Presentation - Cupe Calcina, Eloy Marcelo (2022)
We are pleased to present the sixth issue of Ius Vocatio. Revista de Investigación de la Corte Superior de Justicia de Huánuco, an intellectual organ committed to the dissemination of academic material whose main components are rigor and timeliness. Both are columns that allow us to sustain and encourage the knowledge of law in the current context, a time in which we are overcoming the teachings left by the COVID-19 pandemic to strengthen the justice system both in the Superior Court of Justice of Huanuco and in the Judiciary of the Republic. In this sense, we want to reaffirm our professional commitment to this noble mission of disseminating academic works of our judicial servants, who promote research in the different areas of national and international law.